2023
DOI: 10.3389/fped.2023.1213607
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota alterations in children and their relationship with primary immune thrombocytopenia

Abstract: IntroductionGut microbiota reportedly play a critical role in some autoimmune diseases by maintaining immune homeostasis. Only a few studies have examined the correlation between gut microbiota and the onset of primary immune thrombocytopenia (ITP), especially in children. The purpose of this study was to investigate changes in the composition and diversity of the fecal microbiota of children with ITP, as well as the correlation between such microbiota and the onset of ITP.MethodsTwenty-five children newly dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…However, at the phylum level, we did not find any causal connections between Firmicutes and ITP risk. Another study explored the differences in gut microbiota between children with ITP and healthy individuals, and found a decrease in the proportion of Actinobacteria in the phylum level, which aligns with our findings (Li et al, 2023). There are several reasons to explain the different results, including the vulnerability Scatter plots for the causal association between gut microbiota and ITP (SNP, single nucleotide polymorphism; ITP, immune thrombocytopenia).…”
Section: Discussionsupporting
confidence: 86%
“…However, at the phylum level, we did not find any causal connections between Firmicutes and ITP risk. Another study explored the differences in gut microbiota between children with ITP and healthy individuals, and found a decrease in the proportion of Actinobacteria in the phylum level, which aligns with our findings (Li et al, 2023). There are several reasons to explain the different results, including the vulnerability Scatter plots for the causal association between gut microbiota and ITP (SNP, single nucleotide polymorphism; ITP, immune thrombocytopenia).…”
Section: Discussionsupporting
confidence: 86%
“…A study involving 16 children with ITP showed an increased abundance of Bacteroides and actinomyces in their stool compared to healthy children. This shift in population potentially contributes to the development of ITP by regulating IgG levels [ 12 ]. Remarkably, a study comparing gut flora in BH positive and BH-negative individuals reported alterations in the abundance of Bacteroides and Firmicutes in the former, resembling patterns seen in dysbiotic flora [ 13 ].…”
Section: Discussionmentioning
confidence: 99%